Keragaman Jenis Tanaman Obat Tradisional yang dimanfaatkan oleh Battra di Desa Sepang Kabupaten mempawah - Andesta Chimin Pagea; Fathul Yusro; Yeni Mariani (Jurnal Serambi Engineering, 2022)
The forest in Sepang Village, Mempawah Regency, is still well maintained. This village's battra (traditional healers) used plants found in the forest as medicine to treat or overcome health problems. This research aims to analyze the traditional medicinal plants used by battra in Sepang Village, Toho District, Mempawah Regency. This research uses the survey method by interviewing Battra. Determination of respondents (battra) with purposive sampling techniques. The research results show that battra in Sepang Village still uses 46 traditional medicinal plants, with the highest plant family being Asteraceae (4 types). The highest utilization is found in herb habitus (32.61%), with plant parts in the form of leaves (60.78%), processing by boiling (75.47%), consumption by drinking (87.23%), and plants originating from the yard (56.6%).